Analisis Spasial Kasus Ispa Akibat Kabut Asap Di Wilayah Kerja Uptd Puskesmas Kecamatan Pontianak Utara Tahun 2015 - Mega Lestari, Dwi; , Sri Darnoto S.KM M.PH; , Miftahul Arozaq, S.Si (2016)
Acute Respiratory Infection (ARI) due to the smog is a dangerous disease from year to year in the city of Pontianak. Acute Respiratory Infection (ARI) is Extraordinary Events in the Work Area UPTD District Health Clinics of North Pontianak from year to year. The aims of this study to determine the incidence of Rate Case of Acute Respiratory Infections (ARI) in the Work Area UPTD District Health Clinics of North Pontianak 2015, to determine the characteristics of patients with acute respiratory infection (ARI) in the Work Area UPTD District Health Clinics of North Pontianak and determine distribution cases of Acute Respiratory infections (ARI) as a result of Haze and appropriate health services in the Work Area UPTD District health Clinics of North Pontianak. The method used is descriptive research with observational approach. The study population all populations incidence of Acute Respiratory Infections (ARI).In accordance with the inclusion and exclusion criteria sample of 78 people. The results showed the characteristics of patients with acute respiratory infection (ARI) based on the age of children 5-11 years, adults 26-35 years old and 46-55 year old age. The results showed Incident Rate before the haze of 3,52%, 7,05% smoked during racing, and after haze 2,70%, health facilities spread across North Pontianak District Area there are four health facilities.